STUDY OF HUMAN BEING IN ISLAMIC PHILOSOPHY OF EDUCATION: STUDY OF THE CONCEPT OF FITRAH AND ITS COMPARISON WITH NATIVISM, EMPIRISM, CONVERGENCE AND ITS IMPLICATIONS ON THE ISLAMIC EDUCATION PROCESS - Wahyuningsih, Fitri; Novita, Yanti; Arief, Armai; Zalnur, M. (PT. Antis International Publisher, 2026)
Objective: This study aims to explore the impact of nature on Islamic education, focusing on the concept of fitrah (innate human potential) and its implications for developing a balanced education system that nurtures both cognitive and affective aspects. Method: A library research approach was used, analyzing books, scientific articles, and papers relevant to the topic. Results: The study finds that the concept of fitrah in Islamic educational philosophy emphasizes the intrinsic human potential for knowing God and doing good, which contrasts with the environmental focus of empiricism. The integration of fitrah in Islamic education promotes holistic development, covering intellectual, spiritual, and moral dimensions, advocating for an educational approach that nurtures inborn abilities while fostering morality and spirituality. Novelty: This research contributes to the understanding of how fitrah can be integrated into Islamic educational practices, offering a balanced curriculum, learning methods aligned with Islamic values, and an environment conducive to optimizing human potential. It provides a comparative analysis of fitrah and other philosophical schools, highlighting its unique role in shaping holistic education.